Splitting-free Bioluminescence Imaging Probes and Their Applications - KIM, Sung Bae; FUJII, Rika (BUNSEKI KAGAKU, 2016)
Molecular imaging is recited as a key technology to access the molecular events inside living subjects and is thus a primary research interest among the fields of medicine, pharmacy, biology, environmental science, and chemistry. Molecular imaging provides an ideal toolbox to tackle such multidisciplinary issues including investigation of pathological phenomena, development of new drugs, evaluation of toxicity, etc. However, noninvasive access to such molecular events is a mission impossible as the molecular events occur temporally and do not accompany any detectable optical radiation. During the past decades, a dramatic progress has been achieved in the imaging technology with fluorescent proteins and luciferases, called "reporter". This technology may be categorized into two major groups: (1) a method to temporarily split the reporter protein into two fragments and reconstitute them conditionally, called protein-fragment complementation assay (PCA), and (2) a method to make use of the full length of the reporters as is, i.e., splitting-free. The authors highlight the later molecular imaging strategy utilizing full-length reporter proteins.